The Law in Nazi Germany: Ideology, Opportunism, and the Perversion of Justice - Alan E. Steinweis, Robert D. Rachlin (Berghahn Books, 2013)
Five ot the essays in this book are based on lectures delivered at a symposium on â€œTh e Law in Nazi Germany,â€ which took place at the University of Vermont in April 2009. Organized by the Carolyn and Leonard Miller Center for Holocaust Studies at the University of Vermont, this was the fi fth symposium bearing the name of Carolyn and Leonard Miller, generous supporters of the Centerâ€™s work, and great friends of the university. Established to honor the legacy of Professor Raul Hilberg, who served on the faculty of the University of Vermont for more than three decades, the Miller Center for Holocaust Studies is committed to furthering research and education about the Holocaust, and to serving as a forum for the presentation and discussion of new perspectives on the subject. Hilbergâ€™s pioneering scholarship remains a model and a standard for scholars, and is an inspiration for the Centerâ€™s programming and for publications such as this book. Th e Miller Symposia have contributed signifi cantly to the Centerâ€™s eff orts to explore insuffi ciently charted areas in the history of the Th ird Reich and the Holocaust. Our goal in organizing them has been to address topical, or even controversial, themes in that history, relying on the expertise of some of the most accomplished scholars and other authorities in the fi eld.